Investigation of electromagnetic shielding effectiveness of needle punched nonwoven fabric produced from conductive silver coated staple polyamide fibre - SANCAK, ERHAN; ÖZEN, MUSTAFA SABRİ (TAYLOR & FRANCIS LTD, 2016)
In this paper, electromagnetic shielding effectiveness (EMSE) of needle-punched nonwoven fabric produced from silver-coated staple polyamide fibre having a fineness of 1.7dtex was investigated. This production was carried out at Automatex needle punching line, which consists of carding, cross lapper and needle punching machine. After production, the surface resistivity measurements of needle-punched nonwoven fabric was carried out in accordance with ASTM D 257-07 standard. The EMSE of the as-produced needle-punched nonwoven fabric was determined using a network analyzer as specified in ASTM D4935-10 in the frequency range of 15-3000MHz. Electromagnetic shielding test shows that needle-punched nonwoven fabric produced from 1.7-dtex silver-coated polyamide fibre has the highest shielding value of 36.53dB in the frequency range of 15-3000MHz. The EMSE of needle-punched nonwoven fabric with fibre fineness of 1.7dtex increased from 11.00dB maximum to 36.53dB in the 15-3000 MHz frequency range. It was seen that as the frequency increases, reflection values of the needle-punched nonwoven fabric decrease at floating mode, while absorption values of the nonwoven fabric increase at floating mode in the frequency range of 15-3000MHz. EMSE results of the needle-punched nonwoven fabric produced from 1.7-dtex silver-coated staple polyamide fibres were compared to carbon fabric and needle-punched nonwoven fabric made from stainless steel fibres.
Keywords: silver coated polyamide fibre; needle punching; electromagnetic shielding and nonwoven